Effect of electron‐withdrawing groups on photovoltaic performance of thiophene‐vinyl‐thiophene derivative and benzochalcogenadiazole based copolymers: A computational study - Bhattacharya, Labanya; Sahoo, Smruti R.; Sharma, Sagar; Sahu, Sridhar (International journal of quantum chemistry, 2019)
We report a density functional theory study of the effect of electron‐withdrawing groups such as –F, –CN, –NO2 on the geometrical, optoelectronic, intramolecular charge transfer (ICT), and photovoltaic properties of (E)‐1,2‐bis(5‐alkyl‐[2,3′‐bithiophene]‐2′‐yl)ethene (TVT‐T) based donor‐acceptor (D‐A) copolymers with different acceptor units, that is, benzo[c][1,2,5]thiadiazole, benzo[c][1,2,5]oxadiazole, and benzo[c][1,2,5]selenadiazole. The computed optical absorption spectra of the designed compounds lie in the visible and near‐infrared regions. Of all the studied copolymers, ‐CN substituted and Se‐based compound displays the lowest HOMO‐LUMO (E H ‐ L) gap and optical band gap (E opt). The exciton binding energy (E b) is found to be smaller for O‐incorporated compounds and ‐CN substituted copolymer as well, inferring more ICT. The electron‐hole coherence concentrated over the D‐A units is nearly the same for ‐CN and ‐NO2 substituted compounds, but larger in ‐F derivatives, indicating weak electron‐hole coupling in the formers. Comparatively larger dipole moment (6.421 Debye‐9.829 Debye) and charge transfer length (D CT) (1.976 Å‐3.122 Å) for ‐CN derivatives lead to enhanced ICT properties. The designed donors yield good hole mobilities (0.127‐6.61 cm2 V−1 s−1) and the predicted power conversion efficiencies are calculated to be as high as ~6%‐7% for –CN and –NO2 substituted compounds. The computational study shows that the (E)‐1,2‐bis(5‐alkyl‐[2,3′‐ bithiophen]‐2′‐yl)ethene (TVT‐T) and benzochalcogenadiazole‐based copolymers possess good electronic, photophysical properties and can act as potential donor materials for bulk heterojunction organic solar cell. Incorporation of electron‐withdrawing groups –F, –CN, –NO2 on the chalcogen (S, O, Se) containing acceptor unit improves the photovoltaic performance. The predicted power conversion efficiencies can be reached up to ~6%‐7% for –CN, –NO2 substituted copolymers.